Electrochemistry of single enzymes: fluctuations of catalase activities - Lin, C; Sepunaru, L; Kätelhön, E; Compton, R (American Chemical Society, 2018)
Dynamic fluctuations of the catalytic ability of single catalase enzymes toward hydrogen peroxide decomposition are observed via the nanoimpact technique. The electrochemical signals of single enzymes show that the catalytic ability of single enzymes can temporarily be much higher than expected from the classical, time-averaged Michaelis–Menten description. By combination of experimental data with a new theoretical model, we interpret the unusual enhancement of the single catalase signal and find that single catalases show large fluctuations of the catalytic ability.